Problems with Learning English in a National University: Inbuilt Capacity or National Policy? - Yaakop, Mohd Rizal; Idris, Asmady; Taib, Roslizawati (International Journal of Asian Social Science, 2020)
The objective of this study is to analyze the English learning outcomes of Higher Education students in a national university. Taking Chomsky’s perspective on learning a language, this study is premised on the idea that people develop their grammar and language skill through informal learning process. Each individuals as argued by Chomsky has ‘inbuilt capacity’ to learn certain language since childhood. As method of collecting data, questionnaires were distributed and collected from 113 students from different background in a national university, Universiti Kebangsaan Malaysia (UKM). The respondents were asked to give comments related to English learning program which was done outside their classroom. The result of the study shows a high agreement on the English learning program and this could be seen as answers from the respondent were mainly agreed that English learning program in an ‘off-class’ university environment motivates them to pursue English speaking activities. Students agreed that they were not ashamed of speaking in publics, want to improve their English and most importantly will speak more English in future. Students in national university like UKM, though taken Bahasa Malaysia as a medium of instruction do not neglect the importance of English as international and market language. It is wrong to simply blame students’ problem with their ‘inbuilt capacity’ to learn English. The other factor influencing student most is national policy with regard to official language or medium of instruction at the university. This study implies that university policy must take into account both, national language and English, in order to enhance students’ performance in a job market.